Irisin: A New Code Uncover the Relationship of Skeletal Muscle and Cardiovascular Health During Exercise - Ma, Chunlian; Ding, Haichao; Deng, Yuting; Liu, Hua; Xiong, Xiaoling; Yang, Yi (Frontiers in Physiology, 2021)
Sedentary life style is considered to be a risk factor for cardiovascular disease, while exercise is an effective non-pharmacological intervention to improve cardiovascular health. Irisin, a novel identified peptide secreted mainly by skeletal muscle, has been found involved in the regulation of some metabolic diseases, such as diabetes and obesity, in a hormone-like manner. An emerging number of evidences have shown that the exercise-derived peptide irisin plays an important role in cardiovascular health. However, the relationship between irisin and cardiovascular health is still poorly understood and there are some divergences on the regulation of irisin by exercise. In this review, we present the current knowledge on the origin and physiology of irisin, describe the regulation of irisin by acute and chronic exercise respectively, and discuss the divergence of the related research results. Importantly, we discuss the predictive role of irisin in cardiovascular diseases and describe its treatment and molecular mechanism in some cardiovascular diseases. It is expected that irisin will be used as a therapeutic agent to combat cardiovascular diseases or other disorders caused by inactivity in the near future.